(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The article is devoted to the actual issue of modern world development on the example of the Republic of Kazakhstan. At the present time, the topic of corruption is one of the most discussed in society and in the political arena, at the local and international levels, which brings political science and sociology to the fore in the study of this phenomenon. This is a systemic problem that requires serious study and assessment of its impact on various aspects of life. Conducting a general analysis of modern sociological studies of corruption, we can note the following. Due to the fact that the objective problem of measuring the real picture of the state of corruption is the difficulty of obtaining truthful and objective statistical data, the main tool for sociological research of this phenomenon is interviews and surveys of corruption perception. This principle is fundamental in the main, most well-known studies of corruption. However, sociological research allows us to go beyond the actual corruption and pay attention to other problems related to this industry and no less important. Such as, for example, assessing the impact of corruption on the level and quality of life. Corruption can be characterized as an "unspoken marker" of the state of society, which is sensitive to socio-economic fluctuations and dysfunctions, which in the future can lead to a decrease in the quality of life of the country’s population, thereby leading to the emergence of new, informally supported corruption practices. It examines the methodology used in various sociological studies of corruption, analyzes the approaches to the questionnaire, the most frequently asked questions to respondents. The assessment of the objectivity of sociological surveys of the perception of corruption, as well as their effectiveness in terms of developing measures to improve the standard of living and well-being of the population, is carried out. Key words: bureaucracy, state, business, citizens, corruption research, administrative procedures, sociological research, methodology, sociological survey, raising the standard of living.